UJI PENANGKAPAN PANCING TAJUR MODEL RAWAI VERTIKAL DI PERAIRAN RAWA DESA SUNGAI ULAK KABUPATEN MERANGIN PROVINSI JAMBI - Dani, M.; Maryeni, Sri; Kholis, Muhammad Natsir (Universitas Muara Bungo, 2023)
The number of types of fishing rods in land waters makes it possible to suspect the condition and potential of fisheries by calculating the capture rate (hook rate). Research using a vertical fishing rod that is operated in the ulak river swamp, Nalo Tantan District, Merangin Regency, Jambi Province. The aim of the study was to determine the fishing rod of the straight-line vertical longline model and to analyze the catch. The research method is experimental fishing. The results showed that the vertical standard model rods' capture rate (hook rate) did not meet the standard hook rate value, with an average of 0.04 (not good). The composition of the catch is dominated by nilem fish species (O. vittatus) as much as 71% and the lowest catch of limbat fish (C. nieuhofii) as much as 2%.